Impact of cataract on the livelihood income status of patients availing free cataract surgery in India - Vishwakarma, Pankaj; Mondal, Amit; Ranpise, Dhanaji; Sundararaj, Lijiraj; Shaikh, Shajer; Chavan, Shobhana; Kurian, Elizabeth (International Journal Of Community Medicine And Public Health, 2025)
Background: Cataract remains the leading cause of blindness globally, disproportionately affecting low- and middle-income countries like India. Beyond health consequences, cataract-related visual impairment significantly impacts employment, income, and financial independence. While free cataract surgery programs exist, their effectiveness in restoring economic stability remains underexplored. This study evaluates the socio-economic impact of cataract-induced visual impairment, focusing on employment and earning potential. Methods: A cross-sectional study was conducted across 15 diverse Indian locations, covering urban, semi-urban, and rural areas. A total of 918 patients undergoing free cataract surgery were recruited and interviewed using a structured questionnaire. Data on demographics, employment history, income levels, and willingness to return to work post-surgery were collected. Preoperative visual acuity was categorized into four groups: very good (6/6–6/12), good (<6/12–6/18), borderline (<6/18–6/60), and poor (<6/60). Statistical analysis assessed correlations between vision impairment, economic status, and employment. Results: Among 918 participants, 73% were male, 41% were aged 51–60, and 45% were illiterate. Vision impairment led to financial instability in 75% of cases. Before vision loss, 38% earned ₹5000 to ₹10,000/month, while 18% earned over ₹15,000. After vision deterioration, 19% had no income, and 37% stopped working entirely. Post-surgery, 79% were willing to resume work. Conclusions: Cataract surgery significantly aids economic rehabilitation, with 79% of unemployed patients willing to return to work. Integrating vocational rehabilitation with free surgery programs is crucial for sustainable socio-economic impact, urging policymakers to adopt holistic cataract management strategies.